The influence of emotional intelligence on improving team performance: case study in food crop resilience and horticulture office of north sumatera province - Suma, Dewi (Enrichment : Journal of Management, 2023)
This study aims to determine the effect of emotional intelegence on improving team performance. This research was conducted at Food Crop Resilience and Horticulture Office of North Sumatera Province. This research uses associative research statistics with a quantitative approach with SPSS Program versi 25.0 chosen as the test tool in this study. The sample of this research is totaling 60 people. The measurement method used in this study uses a Likert scale. The application used is simple linear regression in the structural model using test hypotheses and performing data analysis. Based on the results of the study, it can be concluded that emotional intelligence influence on improving team performance, emotional intelligence has a positive and significant effect on improving team performance. The emotional intelligence variable shows that the analysis value of the tcount variable is greater than ttable, (10.949 > 2.009), or sig < (0.05), meaning that the emotional intelligence variable influences team performance at the food crop resilience and horticulture office of North Sumatra Province, thus the hypothesis is accepted